ANIMAL WELFARE IN VANAME SHRIMP (Litopenaeus vannamei) FARMING IN CV. ANUGRAH ABADI PERKASA PONDS WITH DIFFERENT STOCKING DENSITIES - Leonard Yohanes Benedict Cengga; Kadek Lila Antara; Jasmine Masyitha Amelia (Universitas Mataram, 2026)
This study aims to evaluate the application of animal welfare principles in the cultivation of whiteleg shrimp (Litopenaeus vannamei) in the ponds of CV. Anugrah Abadi Perkasa with different stocking densities. This study was motivated by the increasing global market demand for animal welfare standards in aquaculture, while its application in Indonesia is still limited. The method used is descriptive quantitative through direct observation and measurement of observed parameters, as well as active participation supported by documentation. Animal welfare assessment uses a non-invasive approach based on four main indicators, namely environment, nutrition, health, and behavior. The results show that the implementation of animal welfare at CV. Anugrah Abadi Perkasa has been running well in all research plots. The applied cultivation management, such as feed management, water quality control, and disease prevention are able to support optimal shrimp growth and survival. Most of the observed indicators are in the good welfare category. The assessment of nutritional and behavioral indicators in all four plots obtained a score of 1 (good welfare). For environmental and health indicators, the assessment score of 1 (good welfare) is found in plots 1 and 3 with low stocking densities. A score of 2 (tolerable welfare) was found in plots 2 and 4 with high stocking densities, indicating that these conditions are still within tolerable limits, but indicate a decline in environmental quality and health, potentially affecting shrimp growth and survival. This study recommends optimal stocking density management, improved shrimp health management, strengthened animal welfare principles, and the development of more comprehensive evaluation indicators to support the sustainability of whiteleg shrimp farming in Indonesia.